Successful Microablative Fractional Carbon Dioxide Laser Therapy for Vulvar Lichen Sclerosus: A Case Report and Mini-review - Wen-Lin Hsieh; Dah-Ching Ding (Wolters Kluwer Medknow Publications, 2024)
Vulvar lichen sclerosus (VLS) is a chronic inflammatory skin disorder affecting the vulvar region. VLS predominantly affects women, and most cases occur after menopause. Common symptoms include itching, skin-whitening, pain, discomfort, fissures, and scarring. Treatment options include topical steroids, emollients, lifestyle modifications, regular follow-up, and surgical interventions. Carbon dioxide (CO2) laser treatment is a therapeutic option for managing lichen sclerosus. We report a case of VLS successfully treated with a fractional microablative CO2 laser. A 72-year-old female presented with a dry vagina and vulvar itching for 6 months. She visited a local medical clinic, and oral anti-itching medication and topical anti-itching ointment were administered. However, the condition did not improve, and she felt itching. She visited our outpatient department, and a pelvic examination showed bilateral labia minor, revealing a white skin color change and a hardening sensation. The patient was diagnosed with VLS. Microablative fractional CO2 laser therapy was subsequently administered. The treatment course comprised three laser therapy sessions (treatment day, 1 month, and 2 months after the first therapy). The vulvovaginal symptoms questionnaire-21 scores were 14, 6, and 2 for the first, second, and third courses of treatment, respectively. Vulvar itching improved significantly after laser treatment - no more steroid treatment needed. After 10 months of follow-up, the condition of the vulva was maintained well. Although the treatment protocol requires further exploration, CO2 laser treatment could be considered for VLS if topical steroids are ineffective.